Framework for recycling entrepreneurial talent to sustain SMMEs in Botswana - Wilfred Chikukutu; Stephan Van der Merwe (The Southern African Journal of Entrepreneurship and Small Business Management)
Background: Research that interrogates entrepreneurial talent recycling (ETR) is lacking; hence, limited information exists in this regard. Despite the progress made in developing policies and advancing entrepreneurship, the transfer of enterprising expertise within the entrepreneurial context remains a neglected topic.